2019
DOI: 10.3389/fnbeh.2019.00113
|View full text |Cite
|
Sign up to set email alerts
|

Stress Across Generations: DNA Methylation as a Potential Mechanism Underlying Intergenerational Effects of Stress in Both Post-traumatic Stress Disorder and Pre-clinical Predator Stress Rodent Models

Abstract: Although most humans will experience some type of traumatic event in their lifetime only a small set of individuals will go on to develop post-traumatic stress disorder (PTSD). Differences in sex, age, trauma type, and comorbidity, along with many other elements, contribute to the heterogenous manifestation of this disorder. Nonetheless, aberrant hypothalamus-pituitary-adrenal (HPA) axis activity, especially in terms of cortisol and glucocorticoid receptor (GR) alterations, has been postulated as a tenable fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 149 publications
0
12
0
Order By: Relevance
“…Further, given that certain racialized groups are over three times more likely to be in solitary confinement when incarcerated in the US 117 (and are incarcerated at a systematically higher rate), understanding pain responses among single-housed animals as an analog for solitary confinement could highlight pain mechanisms under unmet needs for social contact. Vicarious and intergenerational social stressors have been modeled using vicarious social defeat stress 124 and predator stress during pregnancy to examine epigenetics 8,9 . Inequities in living conditions caused by structural racism can be modeled with manipulations such as fasting or nutrition deprivation, enriched vs. deprived housing 2 , and single vs. multi-animal housing 48 .…”
Section: Social Indicators On Physiological Pain Processesmentioning
confidence: 99%
“…Further, given that certain racialized groups are over three times more likely to be in solitary confinement when incarcerated in the US 117 (and are incarcerated at a systematically higher rate), understanding pain responses among single-housed animals as an analog for solitary confinement could highlight pain mechanisms under unmet needs for social contact. Vicarious and intergenerational social stressors have been modeled using vicarious social defeat stress 124 and predator stress during pregnancy to examine epigenetics 8,9 . Inequities in living conditions caused by structural racism can be modeled with manipulations such as fasting or nutrition deprivation, enriched vs. deprived housing 2 , and single vs. multi-animal housing 48 .…”
Section: Social Indicators On Physiological Pain Processesmentioning
confidence: 99%
“…According to this work, extreme or prolonged stress may affect the transcriptional activity of genes and influence gene expression or suppression in offspring (Lehrner & Yehuda, 2018). Stress exposure in one generation may thus result in epigenetic alterations, creating vulnerability to illness, including psychiatric, in the next generation (Bhattacharya et al, 2019). Yehuda et al (2016) have demonstrated a significant correlation in activation of chemical switches for gene expression associated with PTSD in Holocaust survivors and their offspring.…”
Section: Discussionmentioning
confidence: 98%
“…The study of epigenetic mechanisms that emerge out of traumatic experiences is part of this rapidly growing scientific literature. A number of humanbased epigenetic studies of PTSD have been published (19)(20)(21)(22), with the majority of them focusing on candidate genes which are chosen based on animal models or genetic association findings, such as NR3C1 (23,24), FKBP5 (25,26), SLC6A3 (27), and BDNF (28). For instance, BDNF (brain-derived neurotrophic factor) has been associated with memory, stress, and neuropsychiatric disorders.…”
Section: Epigenetic Markers In Post-traumatic Stress Disordermentioning
confidence: 99%